Prediction of best PCM combinations used in bricks based on their performance for the improvement of thermal performance in energy-efficient building designs by multi-criteria decision - Iachachene, Farida; Cheradi, Hanane; Mougari, Nour Elislam; Kabache, Malika; Dalkilic, Ahmet Selim (ELSEVIER, 2025)
This study investigates the thermal performance of eight-hole bricks enhanced with phase change materials (PCMs), which are gaining popularity as a strategy to enhance thermal comfort and energy performance in buildings, in northern Algerian summer conditions. Three PCMs-capric acid, RT-42, and n-Eicosane-were integrated into the bricks both individually and in various combinations, and their thermal behavior was compared to conventional air-filled bricks. A comprehensive numerical analysis was conducted using the finite volume method coupled with the enthalpy-porosity technique, implemented via a User Defined Function (UDF) in commercial CFD software. The physical model assumed laminar flow, uniform initial brick temperature, and fixed boundary conditions, with a five-day simulation period to capture the dynamics of the region's hot climate. Validation of the numerical model against published data showed a deviation of only 2.48 %, confirming the accuracy and reliability of the computational approach. To determine the optimal PCM configuration, the Multi-Criteria Decision-Making (MCDM) method was applied, evaluating key performance metrics such as peak temperature reduction, heat flux minimization, delay in peak temperature occurrence, and PCM volume optimization. The results demonstrated that the incorporation of PCMs, particularly a combination of capric acid and nEicosane, significantly improved the thermal inertia of the bricks. This configuration achieved a 6.39 % reduction in peak temperature, a 36.49 % decrease in heat flux, and extended the delay in peak temperature occurrence by 5 h. These findings highlight the potential of PCM-enhanced bricks as an effective solution for improving thermal performance in energy-efficient building designs.
Keywords: PCMs; Clay bricks; Hot climate buildings; Thermal comfort; Multi-Criteria Decision-Making; Weighted Sum Method; PHASE-CHANGE MATERIALS; TIME-LAG; WALLS; INSULATION; SELECTION; Energy & Fuels